Effect of Product Innovations on Strategy Implementation Process of Commercial Banks Listed on Nairobi Securities Exchange - Kasiva, Grace Mbuli; Kabui, Anne Christine; Kirimi, Jephitha (American Journal of Strategic Studies, 2023)
Purpose: The purpose of the study was to establish the effect of product innovations on the strategy implementation process of commercial banks listed on Nairobi Securities Exchange. Methodology: The study applied descriptive research design. The study targeted 159 participants including senior managers, credit officers, accountants, human resource managers, operations managers and relationship officers from each of the 11 NSE listed Kenyan commercial banks. The size of sample size was 69 selected using stratified random sampling method. The independent vriable (product innovations) was assessed by looking at new products adopted by banks such as credit cards, insurance products, new deposit accounts and mortgages while dependent variable (strategy implementation process) was assessed through operationalization and institutionalization of strategy. The study utilized research questionnaires for collecting primary data. The distribution of the questionnaires was done by dropping them to the respondents and collecting a week later. Descriptive and" inferential statistics were utilised for data analysis. Findings: The study established the product innovations adopted by the bank were mortgages represented by 97%, credit cards (95%), new deposit accounts (90%) and insurance products (49%). It was established that few banks had embraced insurance products probably because of many insurance agencies in the market. The study found that a unit increase in product innovations results to 0.706 increase in strategy implementation process in commercial banks listed in NSE in Kenya. Unique contribution to theory, practice and policy: The study concluded that product innovations have a substantial effect on strategy implementation process in commercial banks listed in NSE in Kenya The study recommended that managers at banks should consistently make an effort to invest in innovative product designs and modify the current products in order to enhance strategy implementation process. The research also recommends future studies should explore the factors affecting the execution of strategies in financial institutions in Kenya, beyond just commercial banks. This would encompass SACCOS, microfinance institutions, and mortgage companies.